2003
DOI: 10.1093/emboj/cdg195
|View full text |Cite
|
Sign up to set email alerts
|

Importin alpha-regulated nucleation of microtubules by TPX2

Abstract: contributed equally to this workThe importin a-regulated microtubule-associated protein TPX2 is known to be critical for meiotic and mitotic spindle formation in vertebrates, but its detailed mechanism of action and regulation is not understood. Here, the site of interaction on TPX2 for importin a is mapped. A TPX2 mutant that cannot bind importin a is constitutively active in the induction of microtubule-containing aster-like structures in Xenopus egg extract, demonstrating that no other importin a or RanGTPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
208
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(228 citation statements)
references
References 42 publications
18
208
2
Order By: Relevance
“…We found that both importins coimmunoprecipitated with TPX2-FL as expected but not with TPX (319-715) ( Figure 4D). This result was in agreement with the identification of a single functional NLS in TPX2 at position 284 (Schatz et al, 2003). It suggested strongly that in addition to TPX2 other factor(s) regulated by RanGTP were required for microtubule nucleation.…”
Section: Identification Of the Domain In Tpx2 Required For Microtubulsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that both importins coimmunoprecipitated with TPX2-FL as expected but not with TPX (319-715) ( Figure 4D). This result was in agreement with the identification of a single functional NLS in TPX2 at position 284 (Schatz et al, 2003). It suggested strongly that in addition to TPX2 other factor(s) regulated by RanGTP were required for microtubule nucleation.…”
Section: Identification Of the Domain In Tpx2 Required For Microtubulsupporting
confidence: 90%
“…Purified proteins (800 nM) were mixed with soluble tubulin (10 M) and incubated for 20 min at 20°C before fixing and pelleting onto coverslips. As previously reported, GFP-TPX2 formed aggregates with tubulin from which microtubules emanated forming asters (Schatz et al, 2003). We found that the N-terminal domain TPX (1-480) also formed aggregates and microtubule asters (Figure 3).…”
Section: Microtubule Binding Properties and Nucleating Activities Of supporting
confidence: 85%
See 1 more Smart Citation
“…However, the absence of γ-tubulin on mitotic chromatin (except at the kinetochore in certain circumstances, see below) suggests that other proteins may be capable of MT nucleation and therefore may play a role in generating MTs during spindle assembly. Indeed, TPX2 alone appears to nucleate MTs, promote aster formation and bundle MTs in pure tubulin solutions (Schatz et al 2003), a process which is enhanced by the addition of the TPX2 binding partner XRHAMM (Groen et al 2004). Another Ran.GTP-dependent MAP, ISWI, also has MT nucleation and bundling activity in pure tubulin solutions (Yokoyama et al 2009), whilst work in interphase Drosophila tissue culture cells has led to the suggestion that MTs may be nucleated in the absence of γ-tubulin through interaction between tubulin heterodimers and a complex of MAPs, including EB1, Msps and CLIP-190 (Rogers et al 2008).…”
Section: Spatial Regulation Of Mt Nucleationmentioning
confidence: 99%
“…Similarly, TPX2 binds to microtubules and tends to concentrate at the spindle poles (Wittmann et al 1998(Wittmann et al , 2000. It has been shown that TPX2 is required for microtubule nucleation as well as spindle pole organization (Gruss et al 2002;Garrett et al 2002;Schatz et al 2003). Rae1 likewise binds to microtubules (Blower et al 2005) as well as the N-terminal end of NuMA (Wong et al 2006).…”
mentioning
confidence: 99%